Use of a child health surveillance instrument focusing on growth. A cross-sectional study - Araujo, Erika Morganna Neves de; Gouveia, Marcia Teles de Oliveira; Pedraza, Dixis Figueroa (São Paulo Medical Journal, 2017)
BACKGROUND: Proper use of a child health handbook is an important indicator of the quality of care provided to children at healthcare services. This study aimed to evaluate the use of child health surveillance tool (by health professionals?), especially focusing on growth. DESIGN AND SETTING: Cross-sectional study carried out in the context of the Family Health strategy in two municipalities in Paraíba, Brazil. METHODS: Three hundred and twenty-one children under five years of age from areas covered by health workers were included in the study. Mothers answered a questionnaire asking for information on sociodemographic characteristics. Growth charts, records of iron and vitamin A supplementation and notes on immunization schedules registered in the instrument were analyzed. In the case of children for whom the third version of the child health handbook was used, the association between completion of this handbook and sociodemographic characteristics was analyzed. RESULTS: All the parameters studied showed high frequencies of inadequate data entry, ranging from 41.1% for the weight-versus- age chart to 95.3% for the body mass index-versus-age chart. Higher frequency of inadequate data entry was found among children aged 25 months and over and among those living in areas of these municipalities with minimal numbers of professionals in the healthcare teams. CONCLUSIONS: The use of a child health handbook to monitor children’s growth in the municipalities studied appeared to be faulty. Data entry to this instrument was better at locations with larger healthcare teams.